Strain Echocardiography Parameters Correlate With Disease Severity in Children and Infants With Sepsis*. Issue 5 (May 2016) - Haileselassie, Bereketeab; Su, Erik; Pozios, Iraklis; Fiskum, Teresa; Thompson, Reid; Abraham, Theodore
Abstract : Objectives: In the progression of severe sepsis, sepsis-induced myocardial dysfunction contributes to severity of illness and ultimate mortality. Identification of sepsis-induced myocardial dysfunction causing depressed cardiac function during critical illness has implications for ongoing patient management. However, assessing pediatric cardiac function traditionally relies on echocardiographic qualitative assessment and measurement of left ventricular ejection fraction or fractional shortening. These metrics are often insensitive for detecting early or regional myocardial dysfunction. Strain echocardiography is a contemporary echocardiographic modality that may be more sensitive to perturbations in cardiac function. This investigation hypothesizes that strain echocardiography metrics correlate with severity of illness in pediatric sepsis despite normal fractional shortening. Design: Single-center retrospective observational study. Setting: Tertiary 36-bed medical/surgical PICU. Patients: Pediatric patients admitted with sepsis. Interventions: None. Measurements and Main Results: Twenty-three children with sepsis received an echocardiogram in the study period. Patients with sepsis demonstrated abnormal peak systolic longitudinal strain for age (mean = –0.13 ± 0.07; p < 0.01) and low normal peak systolic circumferential strain (mean = –0.17 ± 0.14; p = 0.02) compared with internal controls as well as previously published normal values. Depressed strain was demonstrated in the septic patients despite having normal fractional shortening (mean = 0.41; 95% CI, 0.38–0.43). On initial echocardiographic imaging, worsening peak systolic longitudinal strain was associated with increasing lactate ( p = 0.04). Conclusions: Pediatric patients with sepsis demonstrate evidence of depressed strain echocardiography parameters not shown by fractional shortening that correlate with clinical indices of sepsis severity. Whether strain echocardiography could eventually assist in grading pediatric sepsis severity and affect management is an area for potential future investigation.